Investigation of psychological resilience and care burden of parents caring for children with special healthcare needs in Turkey: A cross-sectional study. - Ceylan, Ali; Demirdel, Ertuğrul (Journal of Pediatric Nursing, 2025)
The study was planned to investigate the resilience and care burden of caregiving parents in Turkey. Demographic and descriptive characteristics were recorded. Psychological resilience was assessed using the Brief Resilience Scale (BRS) and caregiving burden was assessed using the Zarit Caregiving Burden Scale (ZCBS). Independent Sample t- test and ANOVA Mann-Whitney U and Kruskall Wallis tests were used to analyze the data.Multivariate variance analysis was performed with post-hoc tests to determine the differences between the groups. Significance p < 0.05 was accepted. A total of 112 caregivers, 97 of whom were women, with a mean age of 39.84 ± 10.73 years, participated in the study. The mean age of with children with special healthcare needs was 10.83 ± 8.56 years, 61.6 % were male, and 42.9 % had both physical and mental disabilities. In children with special health needs, 41.1 % had mobility limitations, 43.8 % had communication problems, 44.6 % had learning problems and 31.3 % had nutritional problems. The level of mobility limitation, communication, learning and nutrition problems in children with special healthcare needs and the presence of chronic disease or musculoskeletal system problems in caregivers were found to be associated with care burden (p < 0.05). Psychological resilience of caregivers of those with moderate care burden was lower than those with mild care burden (p < 0.05). There was a negative, moderately significant relationship between caregivers' psychological resilience and care burden (r = −0.356; p < 0.001). New strategies should be developed to increase psychological resilience and reduce the burden of care in caregivers of complex children with special healthcare needs. The lived experience of caregivers who support children with special healthcare needs can be improved with psychological and practical care support from health professionals. • The percentage of paternal caregivers participating was 13.4 %. • Psychological resilience of caregiving parents decreases as care burden increases. • There is a negative relationship between caregivers' psychological resilience and care burden. • Mobility limitation, communication, learning and nutritional communication problems increase the burden of care.